2019
DOI: 10.5483/bmbrep.2019.52.4.051
|View full text |Cite
|
Sign up to set email alerts
|

Biological roles and an evolutionary sketch of the GRF-GIF transcriptional complex in plants

Abstract: GROWTH-REGULATING FACTORs (GRFs) are sequence-specific DNA-binding transcription factors that regulate various aspects of plant growth and development. GRF proteins interact with a transcription cofactor, GRF-INTERACTING FACTOR (GIF), to form a functional transcriptional complex. For its activities, the GRF-GIF duo requires the SWITCH2/SUCROSE NONFERMENTING2 chromatin remodeling complex. One of the most conspicuous roles of the duo is conferring the meristematic potential on the proliferative and formative cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 87 publications
(181 reference statements)
2
66
0
Order By: Relevance
“…Similarly, the frequency of explants containing transgenic shoots significantly increased when GRF5 genes were transformed in sunflower, suggesting an effect on proliferation of transformed tissues ( Figure 6 ). The results obtained in these two crops are again consistent with the notion that GRF genes positively regulate cell division in growing plant organs ( Kim, 2019 ). Indeed, Arabidopsis plants overexpressing AtGRF5 develop enlarged leaves containing more cells, which was also accompanied with increased expression of cell cycle genes ( Horiguchi et al., 2005 ; Gonzalez et al., 2010 ; Debernardi et al., 2014 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similarly, the frequency of explants containing transgenic shoots significantly increased when GRF5 genes were transformed in sunflower, suggesting an effect on proliferation of transformed tissues ( Figure 6 ). The results obtained in these two crops are again consistent with the notion that GRF genes positively regulate cell division in growing plant organs ( Kim, 2019 ). Indeed, Arabidopsis plants overexpressing AtGRF5 develop enlarged leaves containing more cells, which was also accompanied with increased expression of cell cycle genes ( Horiguchi et al., 2005 ; Gonzalez et al., 2010 ; Debernardi et al., 2014 ).…”
Section: Discussionsupporting
confidence: 87%
“…Here, we report that ectopic expression of a developmental regulator, GROWTH-REGULATING FACTOR 5 ( GRF5 ), has a positive effect in boosting regeneration and genetic transformation in various crop species using established organogenic or embryogenic regeneration systems. The GRF genes belong to a small plant-specific transcription factor family and they form a transcriptional complex with GRF-INTERACTING FACTOR ( GIF ) to regulate plant growth and development by providing cues to primordial cells of vegetative and reproductive organs ( van der Knaap et al., 2000 ; Kim et al., 2003 ; Omidbakhshfard et al., 2015 ; Kim, 2019 ; Liebsch and Palatnik, 2020 ). Genetic analyses of plants with AtGRF5 overexpression and loss-of-function mutations in Arabidopsis revealed that this transcription factor is involved in the regulation of the cell division and expansion during leaf development ( Horiguchi et al., 2005 ; Horiguchi et al., 2006 ; Debernardi et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been shown that the microRNA miR396 directly inhibits the expression of GRFs through post-transcriptional regulation [11,14]. Constitutive overexpression of Arabidopsis miR396a and miR396b, or heterologous expression of ptc-miR396c (from Populus trichocarpa) and ath-miR396a (from Arabidopsis thaliana) in tobacco (Nicotiana tabacum) significantly reduce mRNA levels of GRFs and lead to narrower and smaller leaves, which mimic Arabidopsis grf1/2/3 [17][18][19][20]. Thus, the transcription levels of GRFs are regulated strictly and quantitatively by the miRNA-GRF-GIF cascade.…”
Section: Introductionmentioning
confidence: 99%
“…The an3-4 and ant-1 mutants were described previously [10,33]. an3-4 has large deletionsin transcribed regions of the AN3 (At5g26840) locus, which occurred by X-ray irradiation.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Another important cell proliferation regulator of organ growth, ANGUSTIFOLIA3/GRF-INTERACTING FACTOR1 (AN3/GIF1), is a member of the transcriptional coactivator family in Arabidopsis [8,9]. AN3/GIF1 is recruited by DNA-binding factors such as GROWTH REGULATOR FACTORs (GRFs) to activate target gene expression [10,11]. Mutations in GRF3, GRF4, or GRF5 have been shown to decrease cell proliferation activity, thereby reducing leaf size [12,13].…”
Section: Introductionmentioning
confidence: 99%